Crime Prediction in the Era of Big - Ait El Bour, Hicham; Amine Talhaoui, Mohamed; Azzouazi, Mohamed; Moulouki, Reda (International Journal of Engineering and Technology, 2018)
Big data has become in recent years the fashion for all companies and academic entities. The appearance of this field of research and discussion on a global scale is due to the development of society where each individual alone produces a large size of data of several types including videos, text, audio, logs, database etc. that are structured or unstructured that even this individual alone cannot be found there. If we cite social media, for example, we find unimaginable data.The fight against crime remains a priority for all societies and deploys enormous human, financial and technological resources to minimize this scourge.If we can know where, who and when with sufficient time lag, we can reach a goal of â€œzero crimes". Hence the need for a crime prediction system.Â Â